MSMES MARKETING STRATEGIES ON COMPETITIVE ADVANTAGE CASE STUDY OF MSMES IN SOUTH LABUHANBATU DISTRICT - Pristiyono; Winda Ardiani; Anggie Yolanda Ritonga; Muda Pardamean Nasution; Ezzah Nahrisah (Journal of Industrial Engineering & Management Research, 2025)
The problems of Micro, Small and Medium Enterprises after Covid-19 include increasing raw material prices, limited human resources, minimal capital, facilities and infrastructure and lack of access to product marketing. Of the many problems that attract the author in this article, access to marketing for Micro, Small and Medium Enterprises products needs more attention from business actors or academics. The purpose of this study was to determine the concept of marketing strategies for Micro, Small and Medium Enterprises in Labuhanbatu Selatan Regency and their impact on competitive advantage and purchasing decisions. The research is included in the quantitative descriptive research model and the author sets the sample to 100 respondents who are Micro, Small and Medium Enterprises that are scattered in South Labuhanbatu Regency. This research was conducted from September - December 2022. The sample withdrawal technique used a purposive sampling approach. All indicators in this study will be tested for validity and reliability. The data analysis technique uses the Structural Equation Modeling (SEM) tool from the IBM SPSS AMOS package in hypothesis testing. Based on the analysis and discussion and testing of the research hypothesis, it was found that 33 respondents had used digital marketing including through social media such as fb, ig, tiktok, wa and others. Based on the results of hypothesis testing, the marketing strategy variable has the most dominant direct impact on competitive advantage and the competitive advantage variable hypothesis test has a direct impact on purchasing decisions. Meanwhile, the marketing strategy variable has no direct impact on purchasing decisions.